The summer nutrient dynamics of Bosherston lakes, Pembrokeshire, and the potential impacts of future climate and policy change - Niciecki, Georgina (Cranfield University, 2008)
Bosherston Lakes, Pembrokeshire have had problems with high nutrient concentrations and algal blooms, particularly in the stream-fed Eastern Arm, leading to the loss of Chara within the Eastern Arm. Management in the last 25 years has led to a reduction in external nutrient loading, but the impact of internal loading during the summer has yet to be properly assessed. The potential impacts of climate and policy change on the nutrient dynamics need to be accounted for to be able to efficiently manage the site in the future to preserve the important Chara habitat. The streams and lake water were analysed for both Total Reactive Phosphorus (TRP) and Total Phosphorus (TP) and Nitrate and Total Nitrogen. The sediment in the lakes were analysed for TRP and TP only. Phosphorus release from sediments and the impact of future temperature changes were assessed through laboratory experiments. It was found that the lakes are still suffering from elevated nutrient levels during the summer. The main source of phosphorus to the lakes in the summer is probably through internal phosphorus release from the lake sediments. The Eastern Arm is the most affected by internal loading. The main sources of nitrates to the lakes are from the streams and groundwater. It was found that phosphorus release increased with increasing temperature. There are many uncertainties but future climate changes are likely to increase both nutrient and sediment loading and it is unlikely that the water quality in the Eastern Arm will improve sufficiently to accommodate Chara. The introduction of an NVZ is unlikely to be counterproductive in terms of reducing N:P ratios and will help decrease nitrate levels in the lakes and streams, some of which are nearing the safe drinking water limits. Future management should target phosphorus loaded sediment entering the lakes in the winter and contributing to the phosphorus concentration in the lake water during the summer when phosphorus is released. The sediment traps in the catchment should be maintained or enhanced and weed cutting should be continued if it is found to have no adverse ecological effects.
Keywords: high nutrient concentrations; algal blooms; external nutrient loading; Total Reactive Phosphorus; Total Phosphorus; Chara